2011
DOI: 10.1177/1090198110385773
|View full text |Cite
|
Sign up to set email alerts
|

A Web-Based Intervention to Reduce Alcohol-Exposed Pregnancies in the Community

Abstract: Despite warnings that drinking during pregnancy is unsafe, many women are still at risk for an alcohol-exposed pregnancy (AEP). This article describes the outcomes of a web-based, self-guided change intervention designed to lower the risk for AEPs in a community. A sample of 458 women, between the ages of 18 and 44 years and at risk for an AEP (i.e., any drinking in the past 30 days and not using reliable contraception), participated in the study. A total of 58% of the women enrolled in the self-guided change … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(34 citation statements)
references
References 45 publications
(59 reference statements)
0
34
0
Order By: Relevance
“…Mass media, 26 print and web based, 11 and three of four interpersonal interventions 10,12,18 showed a positive impact on contraception use. However, identified studies of web, text messaging, and interpersonal interventions did not show a benefit for condom use, other than one text messaging intervention showing increased condom use with new partners only in the prior 3 months.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…Mass media, 26 print and web based, 11 and three of four interpersonal interventions 10,12,18 showed a positive impact on contraception use. However, identified studies of web, text messaging, and interpersonal interventions did not show a benefit for condom use, other than one text messaging intervention showing increased condom use with new partners only in the prior 3 months.…”
Section: Discussionmentioning
confidence: 94%
“…The Gold study from the updated review also showed downsides to text messaging, such as being annoying to participants. 15 The two web-based interventions identified were conducted in combination with other modalities but showed positive effects in contraception use 11 and use of family planning services. 31 Surprisingly, no social media—based interventions were identified either in the prior or current review.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Brief interventions by telephone may be equally successful [29]. Web-based self-directed interventions [30] have also shown promising results, reducing alcohol consumption and increasing effective contraception use among both pregnant and non-pregnant women. However, these might be population-specific in terms of users' opportunities to use the telephone or the Internet and benefit from the interventions.…”
Section: Introductionmentioning
confidence: 99%